2012
DOI: 10.1103/physrevb.85.029904
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Rapid chemical and topological ordering in supercooled liquid Cu46Zr54[Phys. Rev. B83, 094116 (2011)]

Abstract: Erratum: Rapid chemical and topological ordering in supercooled liquid Cu 46 Zr 54 [Phys. Rev. B 83, 094116 (2011)]The constant value for the emissivity (ε), used to calculate C p (T ) [shown in Fig. 7(a)], was incorrectly stated to be ε = 0.2. The actual value used in the calculation was ε = 0.25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…As a consequence of the structural changes, the parameters position and height of the first diffuse maximum of the structure factor of Cu-Zr liquids show a strong dependence on composition and temperature in the simulations which are found to be in accordance with experimental data [13]. Sudden changes of the short-range order upon cooling of liquid Cu 46 Zr 54 were reported recently which were attributed to a rapid development of chemically ordered icosahedral clusters [19].…”
Section: Introductionsupporting
confidence: 83%
“…As a consequence of the structural changes, the parameters position and height of the first diffuse maximum of the structure factor of Cu-Zr liquids show a strong dependence on composition and temperature in the simulations which are found to be in accordance with experimental data [13]. Sudden changes of the short-range order upon cooling of liquid Cu 46 Zr 54 were reported recently which were attributed to a rapid development of chemically ordered icosahedral clusters [19].…”
Section: Introductionsupporting
confidence: 83%
“…The experimental data for liquid (T = 1400 K) and supercooled liquids (T = 1200 K and 1000 K) come from the X-ray diffraction results in Ref. [31]; and those for amorphous solids at 500 K and 300 K, respectively, come from Refs. [28,32].…”
Section: Cluster Type Index Methods (Ctim-3) Analysismentioning
confidence: 99%
“…Adopting a new cluster-type index method (CTIM-3) to analyse the local atomic clusters, it is found that the dominant microstructural configurations in the supercooled liquid and amorphous are the icosahedrons and their combinations, especially the intercross-sharing (IS) clusters linked of two icosahedrons (IS-ICO-clusters) can be used to build some larger IS-ICO nanoclusters with different sizes. Highly interesting, in the system the number of atoms in various IS-ICO nano-clusters demonstrates a magic number sequence of 19,23,25,27,29,31,33,35,37,41,43, and so on. The magic number clusters can be classified into three main types: chain-like, triangle-tailed and quadrilateral-tailed.…”
mentioning
confidence: 99%
“…Although lacking long-range order, metallic liquids do have short-range order (SRO) and medium-range order (MRO), which have been intensely studied in recent years, both experimentally [1][2][3][4][5][6][7][8][9][10][11] and from simulations [12][13][14] . The SRO and MRO are important for understanding the nucleation and growth of crystalline phases 15 and can provide insight into metastable phase and glass formation.…”
Section: Introductionmentioning
confidence: 99%